A Southern Portuguese Margin Perspective of Marine Isotope Stage 47—An Interglacial in the 41 kyr World - Voelker A. H. L.; Rodrigues T.; Trotta S.; Marino M.; Kuhnert H. (Atmosphere, 2022)
In order to better understand interglacial climate variability within the 41 kyr world, we produced high-resolution climate records for interglacial Marine Isotope Stage (MIS) 47 (1424–1452 ka) at IODP Site U1387 (36°48′ N, 7°43′ W) on the southern Portuguese margin. Using benthic and planktonic foraminifera stable isotope records, Uk’37 sea-surface temperature (SST), and plankton assemblage data we investigated Mediterranean Outflow Water (MOW) and surface water conditions. The MOW-level records indicate a poorly ventilated and sluggish bottom current during the MIS 48/MIS 47 transition in association with the insolation maximum, whereas a well-ventilated MOW formed a contourite layer during the second insolation maximum. The benthic δ18O record shows a fairly abrupt change during the deglaciation of MIS 48, while the surface waters experienced a terminal stadial event that was associated with initial cooling and freshening followed by stepwise warming until interglacial SST was reached at 1450 ka. Interglacial conditions with SST of 24 °C or higher persisted until 1427 ka, although warm SST prevailed into MIS 46. The persistent and prolonged warmth is attributed to a northward expansion of the subtropical gyre during MIS 47 as reflected by the dominance of subtropical-tropical planktonic foraminifera species and the presence of warm water coccolithophores taxa.